RELIABLE ADHERENCE TO BEST PRACTICES THAT MITIGATES SYSTEM-LEVEL ERRORS REDUCES COPD READMISSIONS: A SYSTEM REDESIGN USING IMPROVEMENT SCIENCE. Issue 12 (18th November 2016) - Zafar, Muhammad; Panos, Ralph; Warm, Eric; Alessandrini, Evaline
Abstract : Background: Although COPD readmissions adversely affect patient outcomes and health care costs, interventions that reduce readmissions have not been identified. Setting: University of Cincinnati Medical Center, a regional referral, safety net hospital. Objectives: Identify failures in care delivery for COPD patients readmitted within 30 days. Reduce COPD readmissions through system redesign. Methods: We performed a cross-sectional study of COPD 30-day readmissions from 10/2014–3/2015. Readmitted COPD patients were interviewed to identify needs at discharge. We reviewed published literature to identify best practices. We formed a multidisciplinary team to identify a 5-element COPD care bundle designed to mitigate system failures. "Model for Improvement" was used to redesign care delivery. Time-series analysis was performed using statistical process control (SPC) chart. Compliance to bundle components and all-cause 30-day readmissions were observed. Results: There were 52 readmissions among 31 patients. Median time to readmission was 7+7.9 days. COPD was the most common readmission diagnosis (55%), followed by CHF and pneumonia. 42 system-level failures were identified (figure 1). Patient interviews revealed lack of clarity about discharge instructions, including inhaler use. COPD care bundle comprised of; appropriate inhaler regimen, bedside inhaler education, 30-day supply of medications, follow-up within 15 days and standardized discharge instructions. Compliance to COPD care bundle improved over time approaching 90% reliability (figure 2). COPD 30-day all-cause readmission rate decreased from 22.7% to 14.79% with system shift on SPC chart (figure 3). Conclusions: System-level failures and unmet patient needs are modifiable risks for COPD readmissions. Using improvement science to mitigate institution specific system-level failures reduces COPD readmissions.Figure 1 Figure 2 Figure 3